Family in the colombian armed conflict. Challenges and opportunities for attention and strengthening - Moreno-Acero, Iván Darío (2022)
A theoretical reflexive analysis, from the perspective of specialized literature, of the challenges and opportunities for care and support of families who have been victims of the armed conflict in Colombia. This essay is divided into two parts. In the first one, the family is addressed as a social actor which structure and both internal and external dynamics have been affected and transformed by the conflict. In the second part, we consider a set of capacities or potential features to be addressed in order to contribute and support the reconstruction of family dynamics eroded by this extreme stress. The main conclusions indicate that family has been a collective victim during the Colombian armed conflict therefore holistic accompaniment and welcome must be offered to support its healing process. In addition, support shall be given to strengthen its material, political or c ensure care, education, and full development of the human being.